Application of The Two Stay Two Stray Model in The System of Linear Equations Reviewed from Learning Achievement - Zuhriawan, Muhammad Qoyum; Nasrulloh, Muhammad Farid; Khuzaini, Nanang; Umardiyah, Fitri; Habib, Habib (APPLICATION: Applied science in Learning Research, 2024)
The purpose of this study was to determine the increase in student learning achievement with the implementation of the TSTS type cooperative model. Based on initial observations conducted at MTsN 4 Jombang with early interviews with one of the mathematics teachers and several students of MTsN 4 Jombang, several problems were found as follows: There are still students who have not been able to solve Mathematics problems, There are still students who have not been able to understand the process of solving Mathematics problems, then there are some students who have not been able to operate a formula into solving Mathematics problems. The method used in this study is a quantitative method and uses a questionnaire as a data collection tool. The comparative hypothesis testing of two correlated samples, the researcher used calculations with the IBM SPSS Statistics 22 application with a 5% error rate. Based on the research and analysis in section IV, it can be concluded that there is a significant difference in the level of learning achievement of class VIII K students of MTsN 4 Denanyar Jombang before and after implementing the (TSTS) type cooperative learning model. This finding is supported by the paired t-test with a significance result of 0.000, which is lower than the established error level of 0.05